ANALYSIS MSME FINANCIAL MANAGEMENT BASED ON FINANCIAL ACCOUNTING STANDARDS OF SMALL-MEDIUM OF MICRO-ENTITY - Raden Irna Afriani; Dini Martinda Lestari; Rani Puspa; Surachman Surachman (Jurnal Ekonomi, 2022)
Financial statements are a summary of a process of recording financial transactions that occurred during the reporting period and are made to be accountable to the company's owners. The application of accounting to MSMEs is the application of accounting carried out by business actors in managing finances based on SAK EMKM so that they can present good financial reports to help MSME actors know financial information. This study aims to analyze the preparation of financial statements and apply the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) in preparing financial reports.This research includes qualitative research. so that it will produce descriptive data in the form of words. This study uses the financial analysis method for Micro, Small and Medium Enterprises which is reviewed from the Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM) with existing practices in Catering.The preparation of financial reports on Catering is still not good. So far, catering has only relied on records of income from sales and records of cash disbursements. This is due to the absence of a competent workforce in the financial sector. The application of Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM) in catering has not been implemented in preparing its finances, considering that there is no competent workforce and no role for the government in holding MSME actors to provide knowledge and apply applicable accounting standards.